2008
DOI: 10.1093/cvr/cvn356
|View full text |Cite
|
Sign up to set email alerts
|

Coupling factor 6 enhances Src-mediated responsiveness to angiotensin II in resistance arterioles and cells

Abstract: CF6 causes hypertension by directly enhancing Ca2+ signalling in VSMCs and vasoconstriction in the mesenteric arteriolar network via c-Src activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…2h). This is consistent with our previous report that CF6 enhances Ca 2+ signalling in cultured vascular smooth muscle cells and causes vasoconstriction in the mesenteric arteriolar network via c-Src activation [21]. A high-salt diet significantly increased systolic and diastolic blood pressure by 21±3 and 17±3 mmHg, respectively, in transgenic, but not in wildtype mice (p<0.05).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2h). This is consistent with our previous report that CF6 enhances Ca 2+ signalling in cultured vascular smooth muscle cells and causes vasoconstriction in the mesenteric arteriolar network via c-Src activation [21]. A high-salt diet significantly increased systolic and diastolic blood pressure by 21±3 and 17±3 mmHg, respectively, in transgenic, but not in wildtype mice (p<0.05).…”
Section: Resultssupporting
confidence: 92%
“…2d). Recent evidence has also confirmed that the β-subunit is expressed at the surface of cultured vascular endothelial cells and smooth muscle cells [20,21]. Consistent with the distribution of ecto-F 1 F o complex, proton uptake at 15 min after injection of 3 Hlabelled water into the intraperitoneal space was increased in the aorta, kidney, skeletal muscle and liver of transgenic compared with wild-type mice (Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Staining for apoptotic cells 10 The recognition of apoptotic nuclei in paraffin-embedded tissue sections was performed using the ApopMark™ Apoptosis Detection Kit. Briefly, after permeabilizing the samples and inactivating the endogenous peroxidase, terminal deoxynucleotidyl transferase was added to bind to exposed 3'-OH ends of DNA fragments generated in response to apoptotic signals and to catalyze the addition of biotin-labeled deoxynucleotides.…”
Section: Annexin V and Propidium Iodide (Pi) Assay For Apoptosismentioning
confidence: 99%